Nilai-nilai Pendidikan Islam Bagi Anak dalam Tradisi Basiru pada Kegiatan Khitanan - akhairuddin heru (Universitas Islam Negeri (UIN) Mataram, 2020)
This study aims to describe the values ??of Islamic education for children in the local culture that still exists as an educational process in preserving the local culture of the Sekongkang community of West Sumbawa. The urgency of the basic tradition is carried out as a binding value in the Sekongkang community of West Sumbawa, where when another person provides help, that person must provide similar help without having to pay a wage. This is the case with circumcision activities carried out by the people of West Sumbawa in general. The author uses an interpretive approach with an ethnographic writing model. Ethnographic studies describe and interpret cultures, social groups, or systems. Several findings related to the value of education for children such as; Aqidah Educational Values, Character Education Values, Health Education Values??, and Sesks Educational Values. These values ??are instilled by parents to be understood and implemented by the child.